A Case of Nocardiosis with an Unusual Presentation - Hassan Khan, Wahaj Ul; Farid, Ummarah Zafar; Ikram, Mariam; Naseer, Umer; Ali, Kamran (Pakistan Armed Forces Medical Journal, 2022)
Nocardiosis is a neglected, unusual disease caused by aerobic, gram positive, actinomycete in the genus Nocardia. Nocardial infection most often occurs in immunocompromised patients. It has varied geographical distribution and a range of clinical presentations. Lungs are the primary sites of nocardial infection in more than two-third of cases. We report a case from a tertiary care setup in Karachi where nocardiosis occurred in an immunocompetent patient with an isolated CNS involvement.